The effects of financial education on consumer behavior: A study with low-income elderly - Santos, Rafaela Aires Tavares (2021)
Context: This work derives from a participatory research, developed through the implementation of a financial education program for a group of elderly people with an income of up to 2 minimum wages in the city of Palmas - TO. Objective: To discuss the effects of financial education on the financial knowledge and behavior of low-income elderly people. Method: With a qualitative approach, data collection was carried out through focus groups, with transcription and content analysis, as recommended by Bardin (2011). Results: The results showed that the elderly who participated in the program acquired new knowledge about planning and financial organization; developed strategies to organize the domestic budget seeking to reduce indebtedness; used financial control and savings tools to build a healthier habit on personal finances. Conclusion: Financial education practices can contribute to the creation of autonomy and empowerment for the elderly consumer.